Acute exercise and physiological insulin induce distinct phosphorylation signatures on TBC1D1 and TBC1D4 proteins in human skeletal muscle. (23rd December 2013) - Treebak, Jonas T.; Pehmøller, Christian; Kristensen, Jonas M.; Kjøbsted, Rasmus; Birk, Jesper B.; Schjerling, Peter; Richter, Erik A.; Goodyear, Laurie J.; Wojtaszewski, Jørgen F. P.
Abstract : Key points: Phosphorylation signature patterns on TBC1D1 and TBC1D4 proteins in the insulin–glucose pathway were investigated in human skeletal muscle in response to physiological insulin and exercise. In response to postprandial increase in insulin, Akt phosphorylation of T308 and S473 correlated significantly with sites on TBC1D1 (T596) and TBC1D4 (S318, S341, S704). Exercise induced phosphorylation of TBC1D1 (S237, T596) that correlated significantly with activity of the α 2/ β 2/ γ 3 AMPK trimer, whereas TBC1D4 phosphorylation (S341, S704) with exercise correlated with activity of the α 2/ β 2/ γ 1 AMPK trimer. TBC1D1 phosphorylation signatures with exercise/muscle contraction were comparable between human and mouse skeletal muscle, and AMPK regulated phosphorylation of these sites in mouse muscle, whereas contraction and exercise elicited different TBC1D4 phosphorylation patterns in mouse compared with human muscle. Our results show differential phosphorylation of TBC1D1 and TBC1D4 in response to physiological stimuli in human skeletal muscle and indicate that Akt and AMPK may be upstream kinases. Abstract: We investigated the phosphorylation signatures of two Rab‐GTPase activating proteins TBC1D1 and TBC1D4 in human skeletal muscle in response to physical exercise and physiological insulin levels induced by a carbohydrate rich meal using a paired experimental design. Eight healthy male volunteers exercised in the fasted or fed state and muscle biopsies were taken before and immediately after exercise. We identified TBC1D1/4 phospho‐sites that (1) did not respond to exercise or postprandial increase in insulin (TBC1D4: S666), (2) responded to insulin only (TBC1D4: S318), (3) responded to exercise only (TBC1D1: S237, S660, S700; TBC1D4: S588, S751), and (4) responded to both insulin and exercise (TBC1D1: T596; TBC1D4: S341, T642, S704). In the insulin‐stimulated leg, Akt phosphorylation of both T308 and S473 correlated significantly with multiple sites on both TBC1D1 (T596) and TBC1D4 (S318, S341, S704). Interestingly, in the exercised leg in the fasted state TBC1D1 phosphorylation (S237, T596) correlated significantly with the activity of the α 2/ β 2/ γ 3 AMPK trimer, whereas TBC1D4 phosphorylation (S341, S704) correlated with the activity of the α 2/ β 2/ γ 1 AMPK trimer. Our data show differential phosphorylation of TBC1D1 and TBC1D4 in response to physiological stimuli in human skeletal muscle and support the idea that Akt and AMPK are upstream kinases. TBC1D1 phosphorylation signatures were comparable between in vitro contracted mouse skeletal muscle and exercised human muscle, and we show that AMPK regulated phosphorylation of these sites in mouse muscle. Contraction and exercise elicited a different phosphorylation pattern of TBC1D4 in mouse compared with human muscle, and although different circumstances in our experimental setup may contribute to this difference, the observation exemplifies that transferring findings between species is problematic.